Towards anchoring hope - van Louw , T; Beets, PAD (South African Journal of Higher Education, 2011)
Over the last three decades universities across the world have increasingly come under pressure to address inequalities. In South Africa inequalities emanate to a great extent from the country’s apartheid past. It is against this background that the Vice-chancellor of Stellenbosch University commits the institution to ‘education for social responsibility’ and the ‘application of [her] resources to the needs of local and global communities’ as the university repositions itself to contribute to development and equality through what he calls a ‘Pedagogy of Hope’. In this article, Prof Botman’s notion of a Pedagogy of Hope is critically analised against an understanding of the Freirian notion of a Pedagogy of Hope. The authors come to the conclusion that the greatest reason to have hope for Stellenbosch University probably lies in acknowledging that Botman’s ‘Pedagogy of Hope’ emanates from and is embedded in Freire’s idea that hope alone is not sufficient. Hope only becomes meaningful when there is a commitment to move beyond rhetoric towards strategic action – to anchor hope in practice.